2020
DOI: 10.1021/acsomega.0c03585
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Insecticidal Action of Metarhizium anisopliae on Adult Japanese Pine Sawyer Beetles (Monochamus alternatus)

Abstract: Pine wilt disease, caused by Bursaphelenchus xylophilus (pine wood nematode), leads to severe environmental and economic damage. Here, we report the results of experiments on the biological control of pine wilt disease through termination of the insect vector of the nematode and the mechanism of the insecticidal action of Metarhizium anisopliae JEF-279 against Monochamus alternatus (Japanese pine sawyer). A combined treatment with a fungal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…cuniculi, which induced the antioxidant substances glutathione S-transferase (GST), superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) (Gu et al, 2020). The proteins involved in the process can also be extracted and used together with the strains, a fact that was verified for the insecticidal protein serine protease produced by M. anisopliae JEF-279, which accelerated the development of pathogenicity against adults of sawdust beetles (Monochamus alternatus) assisting in the penetration of the insect's body by conidia (Kim et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…cuniculi, which induced the antioxidant substances glutathione S-transferase (GST), superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) (Gu et al, 2020). The proteins involved in the process can also be extracted and used together with the strains, a fact that was verified for the insecticidal protein serine protease produced by M. anisopliae JEF-279, which accelerated the development of pathogenicity against adults of sawdust beetles (Monochamus alternatus) assisting in the penetration of the insect's body by conidia (Kim et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…observed fungal adhesion and penetration to the greasy cutworm, Agrotis ipsilon , larvae using B. bassiana and M. anisopliae . Kim et al 17 . reported that co‐inoculation of M. anisopliae with its culture filtrate containing proteases resulted in higher virulence than that of the fungus alone against adult Japanese pine sawyer beetles, Monochamus alternatus , in which blastospores colonized in the hemocoel and the emerging hyphae in the body wall cuticle were evident within 8 days after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Gabarty et al 12 observed fungal adhesion and penetration to the greasy cutworm, Agrotis ipsilon, larvae using B. bassiana and M. anisopliae. Kim et al 17 reported that coinoculation of M. anisopliae with its culture filtrate containing proteases resulted in higher virulence than that of the fungus alone against adult Japanese pine sawyer beetles, Monochamus alternatus, in which blastospores colonized in the hemocoel and the emerging hyphae in the body wall cuticle were evident within 8 days after treatment. Alkaibari et al 18 reported that when the yellow fever mosquito, Aedes aegypti, was infected by M. brunneum blastospores, adhesion and penetration of the blastospores into the larval cuticle and midgut peritrophic matrix were observed 24 h after inoculation.…”
Section: Introductionmentioning
confidence: 99%
“…The pine sawyer beetle Monochamus alternatus Hope (Coleoptera, Cerambycidae) is a key insect vector of the pinewood nematode, Bursaphelenchus xylophilus (Steiner & Buhrer) Nickle, a destructive forest pest which has caused widespread and destructive pine wilt disease (PWD) throughout Asia and Europe [ 1 3 ]. The pinewood nematode, native to North America (USA and Canada), was first discovered in China in 1982 [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%